Spatial and temporal effects of China’s digital economy on rural revitalization - Zhou, Xiangjun; Du, Meng; Dong, Hai (Frontiers in Energy Research, 2023)
The evaluation index system of China's digital economy and rural revitalization, including 46 indicators of the digital economy and rural revitalization subsystem was constructed. Moreover, the impact of China's digital economy on rural revitalization was analyzed by combining the entropy weight method, Zhou's constraint identification index, spatial Markov analysis, and spatial econometric model. ①The development pattern of the digital economy in China has changed from "multi-point" sporadic distribution to "cluster" aggregation, and the development level of the digital economy in most regions has increased. However, the development of the digital economy has prominent club convergence characteristics, and the development shows a smooth and gradual trend; it is challenging to leapfrog to multi-level development, and neighboring regions influence the development. ② The spatial heterogeneity of the rural revitalization pattern is evident, the characteristics of north-south differences are prominent, the spatial clustering characteristics of the rural revitalization pattern are apparent, and the degree of clustering decreases with the increase of the spatial distance threshold. ③ Digital economic development can significantly promote rural revitalization in the region, and this finding is found to be robust by introducing the exogenous policy shock test of the Outline of Digital Rural Development Strategy. Digital economic development has a significant spatial siphon effect and can influence the level of rural revitalization in neighboring regions. Considering spatial heterogeneity, the regression results based on a multi-distance economic circle show that the siphoning effect of the digital economy on rural revitalization in other regions peaks at 700 km. ④ The effects of digital infrastructure coverage and digital industrialization on the rural revitalization of this region are not significant, and the digital development of industry and digital governance capacity has significant positive effects on the rural revitalization of this region. Implementing differentiated digital economy development strategies and enhancing the radiation of polarized regions are essential to narrowing the regional differences in the digital economy and rural revitalization to realize the coordinated development of China's digital countryside.